Pro Web 2.0 Mashups - Yee, Raymond (Springer, 2017)
How many times have you seen a web site and said, “This would be exactly what I wanted— if only . . . ” If only you could combine the statistics here with data from your company’s earnings projections. If only you could take the addresses for those restaurants and plot them on one map. How often have you entered the date of a concert into your calendar with a single click instead of retyping? How often do you wish that you could make all the different parts of your digital world—your e-mail, your word processor documents, your photos, your search results, your maps, your presentations—work together more seamlessly? After all, it’s all digital and malleable information—shouldn’t it all just fit together? In fact, below the surface, all the data, web sites, and applications you use could fit together. This book teaches you how to forge those latent connections—to make the Web your own—by remixing information to create your own mashups. A mashup, in the words of the Wikipedia, is a web site or web application “that seamlessly combines content from more than one source 1 into an integrated experience. ” Learning how to draw content from the Web together into new integrated interfaces and applications, whether for yourself or for other others, is the central concern of this book.